An investigation of plastic deformation behaviour of Nb-V microalloyed steel produced by powder metallurgy - Gündüz, Süleyman; Taştemür, Demet (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
In this study, Nb-V microalloyed steel was produced and sintered at 1150 °C for 1 h followed by cooling in furnace. While one of the sintered samples was used in the sintered condition, the other one was cooled in air after homogenisation heat treatment at 1150 °C for 1 hour. The remaining samples were deformed at 20%, 40% and 60% in the temperature range 1150-930 °C and then cooled in air. Microstructure and precipitates formation of samples were investigated by optic microscope, scanning electron microscope and energy dispersive spectroscopy analyses. It was observed that samples showed smaller grain size, but higher volume fractions of ferrite under homogenised and 20%, 40% or 60% deformed conditions. This indicated that grain refinement and ferrite formation is accelerated with the deformation which affect the nucleation rate of ferrite. Also, the yield strength, hardness and density increased by the increase in deformation rate.